2019
DOI: 10.5792/ksrr.18.049
|View full text |Cite
|
Sign up to set email alerts
|

Component Alignment in Simultaneous Bilateral versus Unilateral Total Knee Arthroplasty

Abstract: PurposeThe purpose of this study was to investigate differences in component alignment between first and second knees in simultaneous bilateral total knee arthroplasty (SBTKA) and unilateral TKA (UTKA).Materials and Methods274 SBTKAs and 198 UTKAs were included in study. Patients were divided into three groups as SBTKA on the right knee (group A), SBTKA on the left knee (group B) and UTKA (group C). Femoral and tibial component alignment was checked in both coronal plane (alpha [α] and beta [β] angles) and sag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 20 publications
(27 reference statements)
1
7
0
Order By: Relevance
“…In cases of multi-joint problems, the treatment strategy should be established by considering the effect between each joint. Total knee arthroplasty (TKA) is a well-established procedure in osteoarthritic knee patients [4][5][6] and TKA patients commonly present with spinal problems, such as lower back pain (LBP). [2] Although many patients have improved spinal problems after TKA, some complain of aggravated spinal problems or recurrence of knee flexion deformity for the standing body balance, even if it was previously solved with TKA.…”
Section: Introductionmentioning
confidence: 99%
“…In cases of multi-joint problems, the treatment strategy should be established by considering the effect between each joint. Total knee arthroplasty (TKA) is a well-established procedure in osteoarthritic knee patients [4][5][6] and TKA patients commonly present with spinal problems, such as lower back pain (LBP). [2] Although many patients have improved spinal problems after TKA, some complain of aggravated spinal problems or recurrence of knee flexion deformity for the standing body balance, even if it was previously solved with TKA.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretically, in bilateral procedure, the surgical site is exposed to lower temperatures for a total longer duration during sequential surgery, hence there is an increased risk of hypothermia. A study conducted by Qadir et al reported a higher incidence of sequential bilateral TKA compared to staged TKA in Pakistan [ 21 ]. However, more research is required to assess the effect of bilateral TKA on hypothermia.…”
Section: Discussionmentioning
confidence: 99%
“…Total knee arthroplasty (TKA) is a well-established surgical procedure for correcting deformed painful knees, especially those with varus and flexed deformities, and establishing neutral mechanical alignment [ 1 , 2 , 3 , 4 ]. With an increasing aging population, it is common to encounter patients of knee arthritis with concomitant spinal problems because they are the most commonly affected areas due to degenerative changes.…”
Section: Introductionmentioning
confidence: 99%